RETRACTED: Pengaruh Kebijakan Hutang, Profitabilitas Dan Likuiditas Terhadap Nilai Perusahaan Pada Perusahaan Sub Sektor Makanan Dan Minuman Yang Terdaftar Di Bursa Efek Indonesia - Jovie Febriansyah; Elfina Okto Posmaida Damanik (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2022)
RETRACTED NOTICE Following up on the review of articles published in the Ekombis Review Journal carefully, carefully, and considering the article entitled "Pengaruh Kebijakan Hutang, Profitabilitas Dan Likuiditas Terhadap Nilai Perusahaan Pada Perusahaan Sub Sektor Makanan Dan Minuman Yang Terdaftar Di Bursa Efek Indonesia" Vol 10 No S1 (2022): SPECIAL ISSUE DNU 14 TH, DOI: https://doi.org/10.37676/ekombis.v10iS1.1959 This paper was found to violate the Ekombis Review Journal Publication principles and has been withdrawn.This article has been published in the journal Sharia Economics & Economics and the letter of revocation of the article is attached in a PDF.The document and its contents have been removed from the Ekombis Review Journal, and reasonable efforts should be made to remove all references to this article.